Antinociceptive, anti-inflammatory and antipyretic effects of ethanolic root bark extract of Icacina senegalensis in rodents - Esien David-Oku, Godwin Christian Akuodor, Emmanuel Effiong Edet, Godknows K Ogbuji, Juliet Ifeoma Obiajunwa-Otteh, Daniel Ogbonna John Aja (Journal of Applied Pharmaceutical Science, 2016)
To investigate the ethanolic root bark extract of Icacina senegalensis for antinociceptive, anti-inflammatory and antipyretic activities in rats and mice. Acetic acid-induced abdominal constriction and tail immersion tests were used to evaluate the antinociceptive activity of the extract. Egg albumin and carrageenan-induced paw oedema were used to study the anti-inflammatory activity, whereas the anti-pyretic studies were evaluated on yeast and amphetamine-induced pyrexia. The root bark extract (50, 100 and 200 mg/kg) significantly (P
Keywords: Icacina senegalensis, root, pain, inflammation,fever; rats, mice.